Bimbingan Teknis Pencegahan Kekerasan dan Pelecahan Seksual Bagi Siswa SD Ngeri Pacar - Marwati Santoso Putri, Filu (ABDIMAS Madani, 2022)
The worst implication of the freedom to access online content is the contamination of access to pornography in children. In fact, the freedom of access stimulates children to apply the behavior as seen. Pornography addiction in children has a more dangerous impact than drugs because it can damage 5 (five) parts of the human brain, one of which is the Pre Frontal Cortex (PFC) as an important part of controlling moral functions to distinguish good and bad things in decision making. Damage to brain function will end in a child's moral disaster. In accordance with the complaints of teachers and school principals to servants on December 19, 2021, a moral disaster also occurred at the Boyfriend State Elementary School. The school is currently concerned with complaints from students regarding the sexual deviant behavior of some male students by showing their genitals to students when making video calls. Starting from this complaint, the servant conducted a survey of 5th and 6th graders regarding sexual deviance/discomfort behavior experienced during the two years of the pandemic, and it was found that many students received sexual violence from family and friends. The solution presented by the servant to overcome the problems faced by the Boyfriend State Elementary School is to provide technical guidance on the prevention of violence and sexual harassment to the Boyfriend State Elementary School students. It is hoped that students will grow into a healthy and independent young generation if they understand the science and its applications regarding the technical prevention of violence and sexual harassment. The purpose of this PKM activity is to save future generations of Indonesian youth from the bondage of free sex and sexual violence.